Prenatally diagnosed congenital agenesis of the gallbladder: A case report - Jeong-suk Kim; Hee-jung Lee; Eun-jung Koo (Elsevier, 2022)
Congenital agenesis of the gallbladder is a rare malformation of the biliary system. The etiology of the development of gallbladder agenesis is not fully known; malformation during embryonic development is considered its main cause. Although gallbladder agenesis detected in adults during surgery has been reported many times, prenatally diagnosed gallbladder agenesis has rarely been reported. Herein, we report a case of gallbladder agenesis that was diagnosed in a male neonate in the intrauterine period at 26+3 weeks on prenatal ultrasonography (USG). In most cases, the gallbladder is visualized on a follow-up USG performed prenatally or after birth, even if the gallbladder is not seen once during prenatal USG. However, our patient's gallbladder was not visualized in the USG after birth also. Therefore, we performed a hepatobiliary scan and magnetic resonance cholangiopancreatography (MRCP) to find the gallbladder; however, the gallbladder was not visualized. Half of the patients with gallbladder agenesis experience right upper quadrant pain, nausea, or dyspepsia. However, our child did not show any symptoms. This case report will help to manage patients who have no gallbladder.